Genetic Diversity of Perennial Wild Species of Alfalfa Subgenus Falcago (Reichb) Grossh. in Kazakhstan and Their Involvement in the Breeding - Kalibayev, Bauyrzhan Bakytzhanovich; Meiirman, Galiolla Tulendinovich; Yerzhanova, Sakysh Tanyrbergenovna; Abaev, Serik Sarybaevich; Kenebaev, Amankeldi Turgambekovich (AGRIVITA, Journal of Agricultural Science, 2021)
The field expedition has collected 144 samples at the ecotype level of seven wild alfalfa species, which are the source of adaptive properties. One part of the original seeds has been placed for medium-term storage as the gene pool, and the other part has been sown in the culture to use wild-growing species in recurrent breeding. It has been found that the productivity of wild species is inferior to that of M. sativa L., but they are valuable as a source of adaptation traits: drought tolerance, salt tolerance, and winter hardiness, which are important with the development of recurrent breeding to adapt the crops to the global climate change. The yield of the hybrid plants in the offspring from crossing seven ecotypes of M. falcata L. (yellow-flowered) with M. sativa L. (blue-flowered) using a marker-trait has been established: the hybrid nature of the plants obtained from free entomophilic cross-pollination has been established, and the yield of the hybrid plants has amounted to 61 – 91 %. In the hybrid population obtained from M. sativa sybsp. transoxona, M. falcata L., and M. tianschanica Vass. upon crossing them, 50 best phenotypes have been selected to continue the backcrossing with M. sativa L.